2013
DOI: 10.1631/jzus.b1200123
|View full text |Cite
|
Sign up to set email alerts
|

Clinicobiochemical investigations of gangrenous mastitis in does: immunological responses and oxidative stress biomarkers

Abstract: Abstract:A total of 50 does were used to determine selected hematological and biochemical parameters with special references to oxidative stress markers, acute phase protein profiles, and proinflammatory cytokines in healthy and gangrenous mastitis affected does. Animals were divided into two equal groups represented as clinically healthy (control) and diseased groups, respectively. The bacteriological examination of milk samples from diseased does revealed many types of bacterial infection. The isolated bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
6
15
1
2
Order By: Relevance
“…They reported that oxidative stress may induce lipid peroxidation and severe tissue lesions which result in damaged cell organelles, nucleic acids, lipids and proteins. The present findings of oxidative stress are also in harmony with Art et al (1999) and Deaton et al (2004) in horses with recurrent airway obstruction, Ledwozyw & Stolarczyk (1992) in calves with bronchopneumonia, Al-Qudah (2009) in calves with acute pneumonia and in does with gangrenous mastitis (El-Deeb, 2013).…”
Section: Anti-inflammatory Cytokinessupporting
confidence: 81%
“…They reported that oxidative stress may induce lipid peroxidation and severe tissue lesions which result in damaged cell organelles, nucleic acids, lipids and proteins. The present findings of oxidative stress are also in harmony with Art et al (1999) and Deaton et al (2004) in horses with recurrent airway obstruction, Ledwozyw & Stolarczyk (1992) in calves with bronchopneumonia, Al-Qudah (2009) in calves with acute pneumonia and in does with gangrenous mastitis (El-Deeb, 2013).…”
Section: Anti-inflammatory Cytokinessupporting
confidence: 81%
“…Despite the potential value of APPs as stress biomarkers, there are few published studies in rabbits that analyse the relationships between APPs and health status (Sun et al, 2005;Dishlyanova et al, 2011;El-Deeb, 2013). Our hypothesis was that lactation would be a stressful period for female rabbits and that cortisol and APP concentrations in blood would increase.…”
Section: Introductionmentioning
confidence: 91%
“…IGM, is a rare inflammatory breast disease although it is mostly accepted as an autoimmune disease [ 2 ]. In various publications, MTHFR-homozygous 677 TTR mutations [ 6 ], PAI-1 5 G/5 G polymorphism [ 7 ], β-fibrinogen heterozygous 455 G>A mutation [ 8 ], ACE I/D mutation [ 9 ] are reported as closely related with inflammatory, autoimmune events and breast cancer. In the studies, there seem to be a genetic predisposition in the development of many autoimmune and malignant diseases [ 10 ].…”
Section: Discussionmentioning
confidence: 99%